Literature Review: The Effectiveness of Increasing the Family Planning Village Empowerment Program (KB) Against Reducing Birth Rates Through Family Welfare - Darwis; Firnasrudin Rahim; Nurdin Beta; Nur Juliana (Journal of sciences and health, 2022)
Introduction: Family Planning (KB) is a government program designed to balance the needs and the population. The family planning program by the government is so that the family as a small unit of the nation's life is expected to accept the Small Happy and Prosperous Family Norms which are oriented towards balanced population growth. The problem of population and family planning in our country is already so complex and has become a national issue that must be solved. One of the problems that occur is marrying at a young age and the unpreparedness of the couple at the time of marriage poses many health risks to mothers and babies born and the lack of knowledge and education and socialization of child growth and development. The purpose of the family planning village program is to reduce the birth rate for family welfare. Method: This research method is the literature review. Structured literature review using accredited databases such as Science Direct, Scopus, Google Scholar, PudMed, and Garuda. Results: The results of a literature review show that of the 20 journal articles reviewed, 18 journals have village family planning programs t, hat are effective in reducing birth rates for family welfare. Conclusion: Differences in community participation in the effectiveness of village family planning empowerment programs for reducing birth rates and family health caused by age, education, and husband and family support. Keywords: Empowerment, family planning village, welfare, family